Portable heart rate measurement for remote health monitoring system - Mansor, Hasmah; Meskam, Siti Sarah; Zamery, Nasiha Sakinah; Mohd Rusli, Nur Quraisyia Aqilah; Akmeliawati, Rini (IEEE, 2015)
This paper presents a design of portable heart rate monitoring system which is part of a project called Home-smart Clinic. Home-smart Clinic is developed in order to connect medical personnel and patients remotely. Remote health monitoring system is beneficial to the patients and society where the implementation of such system will save hospital bill, waiting time and reduce traffics in the hospital. The prime objective of this paper is to design and develop heart rate measurement device for which real time data could be observed by the doctor via internet. History data could also be acquired; therefore the doctor can interpret the trend of the data to identify the conditions of the patients. In the proposed health monitoring system, heart rate and body temperature wireless sensors were developed, however this paper only focus on heart rate monitoring system. The main components involved in this project are pulse sensor, microcontroller (Arduino with Ethernet shield), and wireless communication device (Xbee). The portable heart rate measurement device was tested to a group of voluntary students. Results showed that the real-time heart rate reading successfully monitored locally (at home) and remotely (at doctor’s computer).